Edible Vaccines - Bhatia, Saurabh (Modern Applications of Plant Biotechnology in Pharmaceutical Sciences, 2015)
Vaccines are considered primary tools for health intervention in both humans and animals. Vaccines can be used more widely, especially in developing countries, if their cost of production can be reduced and they can be preserved without refrigeration. In developing countries certain limitations, like vaccine affordability, the need for “cold chains” from the producer to the site of use of the vaccine, and the dependence on injection, are barriers to health care services. Plant-derived vaccines do not face such limitations. Research under way is dedicated to solving these limitations by finding ways to produce oral (edible) vaccines from transgenic plants. Plant-derived vaccines offer increased safety, envisage low-cost programs for mass vaccination, and propose a wider use of vaccination for veterinary use.